Studi literatur Penerapan Standar Akuntansi Pemerintah pada Laporan Keuangan Daerah - Afifa Anis; Pakpahan, Davit; Nurlinda (Nirta Akuntabel : The Indonesian Journal Of Economic and Accounting, 2026)
This study aims to analyze the implementation of Government Accounting Standards (SAP) on the quality of local government financial statements through a literature review approach. The study employed a literature review method by examining various relevant scientific articles related to the implementation of SAP and the quality of local government financial statements. The results show that the implementation of SAP, particularly accrual-based accounting, has a positive effect on the quality of local government financial statements by improving relevance, reliability, comparability, transparency, and accountability. However, the implementation of SAP has not been fully optimal due to limited human resource competence, inadequate accounting information systems, and low organizational commitment in several regions. Therefore, efforts are needed to improve the competence of government personnel and strengthen supporting systems to ensure the effective and consistent implementation of SAP.